Evolução do mercado de herbicidas em culturas de cana-de-açucar (Saccharum offinarum L.) - Franconere, Ricardo (2010)
Lately, the increase in both sugar and ethanol comsumption has led to an accelerated growth rate of sugarcane cultivated area in Brazil. Herbicides play an important role in weeds control, providing yield gain in an efficient and economical way. The purpose of this study was to evaluate herbicide use over the increasing sugarcane area, by (i) herbicides market evaluation in terms of adoption, treated area, market value and main controlled weeds; (ii) herbicides cost per hectare evaluation; (iii) identification of the main mode of action for sprayed products, and (iv) volume sprayed per hectare evaluation. Market research data collect from 2004 to 2009 in sugar mill was used to perform such analyses. Data was collect by a standard questionnaire and later submitted to statistical analysis in order to come up with an extrapolated market value. There was a significant increase in herbicides treated area in sugarcane, with a consequent greater market value, and that was due to cultivated area growth, once adoption rate did not seem to vary much. When it comes to cost per hectare, it has shown a reduction in the past years. In terms of herbicides mode of action, the most important group is the inhibitors of photosynthesis at PSII. However, the groups that presented the greater market share increase were carotin synthesis inhibitors, PROTOX inhibitors and cell division inhibitors. The only group that presented a reduction of treated area was the inhibitors of photosynthesis I. Even with an increase of herbicides volume, it is not possible to confirm if there is a tendency of gowth or reduction in the amount sprayed per hectare.